2020
DOI: 10.3928/23258160-20200603-03
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Reoperation Rate of Rhegmatogenous Retinal Detachments Occurring During Major Ophthalmology Meetings

Abstract: BACKGROUND AND OBJECTIVE: To investigate whether surgical management of newly diagnosed rhegmatogenous retinal detachment (RRD) varies if patients are diagnosed during a major national ophthalmology conference. PATIENTS AND METHODS: This retrospective cohort study included 34,759 patients with incident RRD, of whom, 1,246 (3.6%) were diagnosed during dates of three national ophthalmology conferences, and 1,170 (3.4%) underwent surgery during conference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
5
2
2
Order By: Relevance
“…The treatment pattern was changed by the presurgery characteristics and surgeons’ considerations during the COVID-19 Pandemic. Contrary to the previous report of higher prevalence of secondary surgeries during the national conference [ 13 ], we achieved a comparable VA outcome and retinal attachment rate in the COVID-19 pandemic group compared with the pre-COVID-19 group, which may suggest that adjustment on the treatment pattern according to patient characteristics and RRD service is effective in treating RRD patients during the COVID-19 Pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The treatment pattern was changed by the presurgery characteristics and surgeons’ considerations during the COVID-19 Pandemic. Contrary to the previous report of higher prevalence of secondary surgeries during the national conference [ 13 ], we achieved a comparable VA outcome and retinal attachment rate in the COVID-19 pandemic group compared with the pre-COVID-19 group, which may suggest that adjustment on the treatment pattern according to patient characteristics and RRD service is effective in treating RRD patients during the COVID-19 Pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports focusing on RRD progression found that prolonged preoperative waiting time is related to the development of macular-off RRD [ 5 ], irreversible macular damage [ 6 8 ], proliferative vitreoretinopathy (PVR) progression [ 9 ], and development of choroidal detachment (CD) [ 10 ]. In addition, previous studies have shown that during national meetings or holiday-time, reduced staffing is often associated with adverse patient outcomes, changes in treatment patterns, and care delays in acute cardiovascular conditions [ 1 , 11 , 12 ] and RRD patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment pattern was changed by the presurgery characteristics and surgeons' considerations during the COVID-19 pandemic. Contrary to the previous report of higher prevalence of secondary surgeries during the national conference [7], we achieved a comparable VA outcome and retinal attachment rate in the COVID-19 pandemic group compared with the pre-COVID-19 group, which may suggest that adjustment on the treatment pattern according to patient characteristics and RRD service is effective in treating RRD patients during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with RRD are considered emergency cases and are reported to receive surgery 1–7 days after the onset of symptoms [ 5 , 12 14 ]. During Beijing’s top-level COVID-19 emergency response, the 14-day quarantine period led to prolonged presurgical waiting times in the COVID-19 pandemic group (28days vs. four days).…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to irreversible visual damage if it is not treated in time [ 4 ]. RRD patients experiencing long delays for surgery are considered more likely to undergo a second surgery within 30 days of the primary procedure [ 5 ].…”
Section: Backgroundsmentioning
confidence: 99%